Mothers’ and fathers’ engagement in math activities with their toddler sons and daughters: The moderating role of parental math beliefs - Silver, Alex M.; Chen, Yu; Smith, Darcy K.; Tamis-LeMonda, Catherine S.; Cabrera, Natasha; Libertus, Melissa E. (Frontiers in Psychology, 2023)
Parents’ beliefs about the importance of math predicts their math engagement with their children. However, most work focuses on mothers’ math engagement with preschool- and school-aged children, leaving gaps in knowledge about fathers and the experiences of toddlers. We examined differences in mothers’ and fathers’ (N=94) engagement in math- and non-math activities with their two-year-old girls and boys. Parents of sons did not differ in their engagement in math activities from parents of daughters. Mothers reported engaging more frequently in math activities with their toddlers than fathers did, but the difference reduced when parents endorsed stronger beliefs about the importance of math for children. Even at very early ages, children experience vastly different opportunities to learn math in the home, with math-related experiences being shaped by both parent gender and parents’ beliefs.